2021
DOI: 10.21037/jgo-21-116
|View full text |Cite
|
Sign up to set email alerts
|

Ablative radiation therapy for hepatocellular carcinoma is associated with reduced treatment- and tumor-related liver failure and improved survival

Abstract: Background: More than 70% of patients with hepatocellular carcinoma (HCC) are not candidates for curative therapy or recur after curative-intent therapy. There is growing evidence on the use of ablative radiation therapy (RT) for liver tumors. We aimed to analyze outcomes of HCC patients treated with conventional versus ablative RT. Methods:We retrospectively analyzed medical records of HCC patients treated with liver RT from 2001 to 2019. We defined ablative RT as biologically effective dose (BED) ≥80 Gy. REC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“… 2 , 3 More recently, image-guided RT using computed tomography (CT) and magnetic resonance imaging (MRI), improved motion management, and highly conformal techniques such as intensity-modulated radiation therapy (IMRT) and stereotactic body radiation therapy (SBRT) have made definitive irradiation of HCC more feasible. 2 , 4 , 5 CT-guided RT may either be accomplished with cone beam computed tomography (CBCT) or CT-on-rails. 6 , 7 On-board CT or MRI improves daily treatment position by allowing one to visualize the patient's liver contour near the tumor target volume.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 More recently, image-guided RT using computed tomography (CT) and magnetic resonance imaging (MRI), improved motion management, and highly conformal techniques such as intensity-modulated radiation therapy (IMRT) and stereotactic body radiation therapy (SBRT) have made definitive irradiation of HCC more feasible. 2 , 4 , 5 CT-guided RT may either be accomplished with cone beam computed tomography (CBCT) or CT-on-rails. 6 , 7 On-board CT or MRI improves daily treatment position by allowing one to visualize the patient's liver contour near the tumor target volume.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results from the RTOG-1112 trial at the ASTRO 2022 meeting also demonstrated improved OS, PFS and TTP when combining SBRT followed by sorafenib vs. sorafenib alone. Promising findings on ablative radiation therapy could mean significantly improved outcomes for patients with unresectable HCC [ 73 , 74 , 75 ]. Currently, several ongoing clinical trials intend to assess the outcomes of combining systemic therapy with radiation therapy (e.g., NCT04857684, NCT04913480, NCT04167293, NCT05286320).…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of SBRT over IMRT are its ability to deliver higher radiation doses per treatment and its shorter overall treatment time [ 72 ]. Radiation treatment with either SBRT or fractionated RT can be ablative at a higher biologically effective dose (BED) (≥80 Gy), and was shown to improve hepatic tumor control, and possibly improve overall survival by preventing liver failure originating from tumor progression, when compared with the delivery of a lower BED in HCC patients ineligible for curative therapies ( Table 3 ) [ 73 ]. In patients with intrahepatic cholangiocarcinoma (ICC), a higher BED (>80.5 Gy), when compared to lower doses, was associated with significantly better 3-year OS (73% vs. 38%, respectively; p = 0.17) and 3-year LC (78% vs. 45%, respectively; p = 0.04; Table 3 ) [ 74 ].…”
Section: Locoregional Therapiesmentioning
confidence: 99%
“…Local control of HCC in the liver is crucial to slow or prevent disease progression, and subsequent progression to liver failure. Although modern series of photon stereotactic ablative RT have shown excellent local control outcomes in the treatment of HCC [ 95 ], protons have dosimetric advantages, especially in certain clinical scenarios. There is a growing body of evidence supporting the use of proton therapy for HCC [ 26 , 46 , 47 , 55 , 57 , 58 , 67 ].…”
Section: Discussionmentioning
confidence: 99%